10y2=3-1y

Finding the LCD of a list of values is the same as finding the LCM of the denominators of those values.

y2,1,y

Since y2,1,y contain both numbers and variables, there are two steps to find the LCM. Find LCM for the numeric part 1,1,1 then find LCM for the variable part y2,y1.

The LCM is the smallest positive number that all of the numbers divide into evenly.

1. List the prime factors of each number.

2. Multiply each factor the greatest number of times it occurs in either number.

The number 1 is not a prime number because it only has one positive factor, which is itself.

Not prime

The LCM of 1,1,1 is the result of multiplying all prime factors the greatest number of times they occur in either number.

1

The factors for y2 are y⋅y, which is y multiplied by each other 2 times.

y2=y⋅y

y occurs 2 times.

The factor for y1 is y itself.

y1=y

y occurs 1 time.

The LCM of y2,y1 is the result of multiplying all prime factors the greatest number of times they occur in either term.

y⋅y

Multiply y by y.

y2

y2

Multiply each term in 10y2=3-1y by y2 in order to remove all the denominators from the equation.

10y2⋅y2=3⋅y2-1y⋅y2

Cancel the common factor of y2.

Cancel the common factor.

10y2⋅y2=3⋅y2-1y⋅y2

Rewrite the expression.

10=3⋅y2-1y⋅y2

10=3⋅y2-1y⋅y2

Simplify each term.

Cancel the common factor of y.

Move the leading negative in -1y into the numerator.

10=3y2+-1y⋅y2

Factor y out of y2.

10=3y2+-1y⋅(y⋅y)

Cancel the common factor.

10=3y2+-1y⋅(y⋅y)

Rewrite the expression.

10=3y2-1⋅y

10=3y2-1⋅y

Rewrite -1y as -y.

10=3y2-y

10=3y2-y

10=3y2-y

Rewrite the equation as 3y2-y=10.

3y2-y=10

Move 10 to the left side of the equation by subtracting it from both sides.

3y2-y-10=0

Factor by grouping.

For a polynomial of the form ax2+bx+c, rewrite the middle term as a sum of two terms whose product is a⋅c=3⋅-10=-30 and whose sum is b=-1.

Factor -1 out of -y.

3y2-(y)-10=0

Rewrite -1 as 5 plus -6

3y2+(5-6)y-10=0

Apply the distributive property.

3y2+5y-6y-10=0

3y2+5y-6y-10=0

Factor out the greatest common factor from each group.

Group the first two terms and the last two terms.

(3y2+5y)-6y-10=0

Factor out the greatest common factor (GCF) from each group.

y(3y+5)-2(3y+5)=0

y(3y+5)-2(3y+5)=0

Factor the polynomial by factoring out the greatest common factor, 3y+5.

(3y+5)(y-2)=0

(3y+5)(y-2)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

3y+5=0

y-2=0

Set the first factor equal to 0 and solve.

Set the first factor equal to 0.

3y+5=0

Subtract 5 from both sides of the equation.

3y=-5

Divide each term by 3 and simplify.

Divide each term in 3y=-5 by 3.

3y3=-53

Cancel the common factor of 3.

Cancel the common factor.

3y3=-53

Divide y by 1.

y=-53

y=-53

Move the negative in front of the fraction.

y=-53

y=-53

y=-53

Set the next factor equal to 0 and solve.

Set the next factor equal to 0.

y-2=0

Add 2 to both sides of the equation.

y=2

y=2

The final solution is all the values that make (3y+5)(y-2)=0 true.

y=-53,2

y=-53,2

The result can be shown in multiple forms.

Exact Form:

y=-53,2

Decimal Form:

y=-1.6‾,2

Mixed Number Form:

y=-123,2

Solve for y 10/(y^2)=3-1/y